Evidências acerca da visita familiar ampliada em Unidade de Terapia Intensiva adulto. - Gomes, Iago Vieira; Gouveia Neto, José Rocha; Gonçalves, Nataly da Silva; de Souza, Maurício Caxias; Martins, Douglas Silva; da Rocha Leal, Natália Pessoa (Enfermagem Brasil, 2022)
Objective: To analyze the scientific evidence about extended family visits in adult intensive care units. Methods: Integrative review carried out in July 2021. The descriptors "intensive care", "humanization" and "patient visits" were used. Distributed in the Nursing Database, Scientific Electronic Library Online, Medical Literature Analysis and Retrieval System Online, Latin American and Caribbean Health Sciences Literature; available in English, Portuguese or Spanish, between 2016 to July 2021, obtaining a total of nine viable articles that fit the research objective. Results: In view of the analysis of the studies, it was identified that the extended visit to the intensive care units reduced anxiety and stress factors on the part of family members, without an increase in infection rates; however, it had no significant impact on events such as delirium. Conclusion: The presence of family members in the intensive care unit allows an evolution in the psychosocial condition, in the reduction of stress and anxiety regarding the disease. However, the benefits for the clinical condition are few, and more studies are needed to observe the phenomenon.